2024
DOI: 10.3102/01623737231221155
|View full text |Cite
|
Sign up to set email alerts
|

Feeling the Threat of Race in Education: Exploring the Cultural Politics of Emotions in CRT-Ban Political Discourses

Rican Vue,
Katrya Txay Ly,
Tori Porter
et al.

Abstract: Recent attacks on critical race theory (CRT) aim to limit discussion and understanding of race (and its intersection with class, gender, and power). Racial dialogues can be uncomfortable for those who benefit from power, suggesting that resistance to CRT or any discussion of race and power in education is rooted in emotions. This study examines the role of racialized emotions in public policy discourse that surrounds CRT bans in education that have been proposed, and in many cases, passed across the United Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 95 publications
0
11
0
Order By: Relevance
“…Examples from other authors in this special issue also demonstrate what happens when students of color's interests are put last. Vue et al (2024), through critical discourse analysis, describe what it looks like to center the emotions of "white" individuals, which results in white students avoiding discussions of race to ease their own discomfort. They explore the discourse around recent bans on critical race theory (CRT).…”
Section: (Re)designing Policies To Prioritize the Needs Of The Most V...mentioning
confidence: 99%
“…Examples from other authors in this special issue also demonstrate what happens when students of color's interests are put last. Vue et al (2024), through critical discourse analysis, describe what it looks like to center the emotions of "white" individuals, which results in white students avoiding discussions of race to ease their own discomfort. They explore the discourse around recent bans on critical race theory (CRT).…”
Section: (Re)designing Policies To Prioritize the Needs Of The Most V...mentioning
confidence: 99%
“…It also enables researchers to explore how language then establishes, cultivates, and maintains (or resists) existing power structures and ideologies through its influence on practice, social interactions, and institutions. Vue et al (2024) engage in what they describe as a close reading of public policy discourse to examine the kinds of emotions that are tacitly endorsed, invited, and animated within racialized politics and their impact.…”
Section: Attributes Of Critical Education Policy Research Employed In...mentioning
confidence: 99%
“…Rather, they are "imbued with crime-related meaning and imagery," the same kinds of meaning and imagery used to dehumanize certain populations and to justify violence in genocide, colonization, and slavery. Vue et al (2024) found that a race-evasive notion of equity and love was used to support CRT bans in four of the states under investigation. To illustrate, a romanticized notion of loving all equally was used to whitewash or erase systematic mistreatments that indelibly mark minoritized groups.…”
Section: Attributes Of Critical Education Policy Research Employed In...mentioning
confidence: 99%
“…In "Feeling the Threat of Race in Education," Vue et al (2024) provide a timely analysis of the "anti-Critical Race Theory" bills being proposed and passed in state legislatures across the United States. They examine the discourse in legislative sessions in four states-Idaho, North Dakota, Oklahoma, and Tennessee-early adopters of these bans.…”
Section: The Contributions Of Articles In This Special Issuementioning
confidence: 99%
“…Finally, researchers should look to other fields and disciplines to enhance and elaborate education policy, as many of the examples here do. Daramola (2024), for example, bridges the concept of Black radical imaginaries with education policy, Nichols and Dixon-Román (2024) connect critical platform studies with policy analysis, and Vue et al (2024) connect emotions to analysis of policy discourses in their work on anti-Critical Race Theory legislation. There are endless possibilities for bridging critical theories with quantitative and mixed methods or using emerging critical ideas in other fields and disciplines to study schools.…”
Section: Bridging Critical Policy Analysis and "Traditional" Approachesmentioning
confidence: 99%